Analisis Semiotika Pesan Dakwah Dalam Film Animasi Nussa dan Rarra Episode Nussa Bisa - Aiti Fatma; Ida Afidah (UNISBA Press, 2022)
Abstract. Film is an important medium’s of da’wah, because it is an audio-visual media that can be enjoyed anywhere and anytime. The animated film Nussa and Rarra episode Nussa can tell the story of Nussa's desire to participate in a football match despite her physical limitations. The purpose of this research is to find out the message of aqidah, shari'ah and morals da'wah contained in the film. This study uses a qualitative type with semiotic analysis method Roland Barthes model by examining the signs and markers in the film. The results of the study showed several da'wah messages including: aqidah; Allah does not look at the physical but the heart, accepts everything sincerely. Shari'ah; obligation to wear hijab, start activities with basmallah. Morals; kissing parents' hands, caring for sick parents, knocking on doors before entering, speaking kind words to parents. Abstrak. Film adalah media dakwah yang penting, sebab ia merupakan media audio-visual yang dapat dinikmati dimana saja dan kapan saja. Film animasi Nussa dan Rarra episode Nussa bisa mengisahkan tentang keinginan Nussa untuk mengikuti pertandingan sepak bola walapun dengan keterbatasan fisik yang dimilikinya. Tujuan dari penelitian ini untuk mengetahui pesan dakwah aqidah, syari’ah dan akhlak yang terkandung dalam film tersebut. Penelitian ini menggunakan jenis kualitatif dengan metode anlisis semiotika model Roland Barthes dengan mengkaji tanda dan petanda dalam film tersebut. Hasil penelitian menunjukkan beberapa pesan dakwah diantaranya: aqidah; Allah tidak memandang fisik melainkan hati, menerima segala sesuatu dengan ikhlas. Syari’ah; kewajiban berhijab, memulai aktifitas dengan basmallah. Akhlak; mencium tangan orangtua, merawat orangtua yang sakit, mengetuk pintu sebelum memasukinya, bertutur kata baik kepada orangtua.